Targeting the NLRP3 inflammasome and associated cytokines in scleroderma associated interstitial lung disease - Woo, Samuel; Gandhi, Shifa; Ghincea, Alexander; Saber, Tina; Lee, Chris J.; Ryu, Changwan (Frontiers in Cell and Developmental Biology, 2023)
SSc-ILD (scleroderma associated interstitial lung disease) is a complex rheumatic disease characterized in part by immune dysregulation leading to the progressive fibrotic replacement of normal lung architecture. Because improved treatment options are sorely needed, additional study of the fibroproliferative mechanisms mediating this disease has the potential to accelerate development of novel therapies. The contribution of innate immunity is an emerging area of investigation in SSc-ILD as recent work has demonstrated the mechanistic and clinical significance of the NLRP3 inflammasome and its associated cytokines of TNFα (tumor necrosis factor alpha), IL-1β (interleukin-1 beta), and IL-18 in this disease. In this review, we will highlight novel pathophysiologic insights afforded by these studies and the potential of leveraging this complex biology for clinical benefit.